2007
DOI: 10.1080/01913120601169477
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Characteristics of Human Mesenchymal Stromal (Stem) Cells Derived from Bone Marrow and Term Placenta

Abstract: Human mesenchymal stromal (stem) cells (hMSCs) isolated from adult bone marrow (BM-hMSCs) as well as amnion (AM-hMSCs) and chorion (CM-hMSCs) term placenta leaves were studied by transmission electron microscopy (TEM) to investigate their ultrastructural basic phenotype. At flow cytometry, the isolated cells showed a homogeneous expression of markers commonly used to identify hMSCs, i.e., CD105, CD44, CD90, CD166, HLA-ABC positivities, and CD45, AC133, and HLA-DR negativities. However, TEM revealed subtle yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
78
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 20 publications
15
78
0
2
Order By: Relevance
“…Again, ultrastructural investigation revealed a strict resemblance with MSCs. After culturing, these cells showed a multivacuolar appearance and a high synthetic competence, that is, prominence of rough endoplasmic reticulum, as we recently observed in MSCs derived from the human bone marrow [17].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Again, ultrastructural investigation revealed a strict resemblance with MSCs. After culturing, these cells showed a multivacuolar appearance and a high synthetic competence, that is, prominence of rough endoplasmic reticulum, as we recently observed in MSCs derived from the human bone marrow [17].…”
Section: Discussionsupporting
confidence: 70%
“…Details are provided in the supplemental online material. As already described [17], cells were also collected in Eppendorf tubes immediately after detachment; pellets were processed for electron microscopy as described in the supplemental online material.…”
Section: Cell Isolation Culture and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells had a relatively high nuclear/ cytoplasm (N/C) ratio, prominent nucleoli, premature cytoplasmic organelles, and numerous filipodia. These characteristics are similar to those of bone marrow-derived mesenchymal stem cells (Pasquinelli et al, 2007). hADMSC morphology including cell size, shape, nuclear density, and cytoplasmic contents varied in this study.…”
supporting
confidence: 78%
“…In addition, UCBMSCs showed more abundant rER than BMMSCs. In previous studies, no differences have been found in mitochondrial number or structure and, to our knowledge, this is the first time that the difference in mitochondrial-to-cytoplasm area ratio has been demonstrated between these hMSC types [42]. Since the mitochondrial-tocytoplasm area ratio also increased after 14-days osteoinduction in all hMSC types and the increase was most striking in BMMSC > 50, we believe that the higher mitochondrial-to-cytoplasm area ratio in UCBMSC and BMMSC < 18 compared with BMMSC > 50 could indicate different overall maturation levels of these cells.…”
mentioning
confidence: 56%